Overexpression, purification, crystallization and preliminary X-ray analysis of Rv2780 from Mycobacterium tuberculosis H37Rv - Tripathi, Sarvind Mani (International Union of Crystallography, 2008)
Rv2780, an alanine dehydrogenase from Mycobacterium tuberculosis (MtAlaDH), catalyzes the NAD-dependent interconversion of alanine and pyruvate. Alanine dehydrogenase is released into the culture medium in substantial amounts by virulent strains of mycobacteria and is not found in the vaccine strain of tuberculosis. Crystals of recombinant MtAlaDH were grown from 2 M ammonium sulfate solution at ∼12 mg ml(−1) protein concentration in two crystal forms which occur in the presence and absence of NAD/pyruvate, respectively. Diffraction data extending to 2.6 Å were collected at room temperature from both apo and ternary complex crystals. Crystals of the apoenzyme have unit-cell parameters a = 173.89, b = 127.07, c = 135.95 Å. They are rod-like in shape and belong to space group C2. They contain a hexamer in the asymmetric unit. Crystals of the ternary complex belong to space group P4(3)2(1)2 and have unit-cell parameters a = b = 88.99, c = 373.85 Å. There are three subunits in the asymmetric unit of the holoenzyme crystals.